2017
DOI: 10.5194/soil-3-211-2017
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and limitations related to the application of plant-derived lipid molecular proxies in soil science

Abstract: Abstract. The application of lipids in soils as molecular proxies, also often referred to as biomarkers, has dramatically increased in the last decades. Applications range from inferring changes in past vegetation composition, climate, and/or human presence to unraveling the input and turnover of soil organic matter (SOM). The molecules used are extractable and non-extractable lipids, including ester-bound lipids. In addition, the carbon or hydrogen isotopic composition of such molecules is used. While holding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 224 publications
(228 reference statements)
1
44
0
Order By: Relevance
“…The lipids from fresh leaves as well as O and A horizons showed even-over-odd predominance in long-chain fatty acids (> n-C 22 : 0 ) and odd-over-even predominance in nalkanes (> n-C 23 ), a property usually ascribed to the lipids derived from higher plant biomass (Eglinton et al, 1962;Kolattukudy et al, 1976;Amblès et al, 1994a). To quantify this pattern of the chain length preference, carbon preference index (CPI) values were also calculated (Eglinton et al, 1962).…”
Section: Concentration Of Biomarkersmentioning
confidence: 99%
“…The lipids from fresh leaves as well as O and A horizons showed even-over-odd predominance in long-chain fatty acids (> n-C 22 : 0 ) and odd-over-even predominance in nalkanes (> n-C 23 ), a property usually ascribed to the lipids derived from higher plant biomass (Eglinton et al, 1962;Kolattukudy et al, 1976;Amblès et al, 1994a). To quantify this pattern of the chain length preference, carbon preference index (CPI) values were also calculated (Eglinton et al, 1962).…”
Section: Concentration Of Biomarkersmentioning
confidence: 99%
“…Fully understanding the way in which plant leaf waxes reflect their environment could give an insight into plant resilience to future climate change (Guo, Guo, He, & Gao, ) and is instrumental for reconstructing past environmental conditions (Jansen & Wiesenberg, ). The n‐ alkane fraction of the leaf wax, typically in the range of C 20 and C 37 (Eglinton & Hamilton, ), in particular has been suggested as a proxy for past environments due to their resistance to degradation (Jansen & Wiesenberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fully understanding the way in which plant leaf waxes reflect their environment could give an insight into plant resilience to future climate change (Guo, Guo, He, & Gao, ) and is instrumental for reconstructing past environmental conditions (Jansen & Wiesenberg, ). The n‐ alkane fraction of the leaf wax, typically in the range of C 20 and C 37 (Eglinton & Hamilton, ), in particular has been suggested as a proxy for past environments due to their resistance to degradation (Jansen & Wiesenberg, ). Studies measuring n‐ alkane patterns across plant communities, functional groups, genera, and species have shown that the n‐ alkane pattern seems to be influenced by several environmental factors, notably temperature and precipitation (Bush & McInerney, , ; Feakins et al, ; Hoffmann, Kahmen, Cernusak, Arndt, & Sachse, ; Sachse, Radke, & Gleixner, ; Tipple & Pagani, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that only the soil n-alkane signal reflects changes in CPI, which suggests that the processes leading to changes in CPI are related to soil processes. Potentially, such a process could be the de-novo genesis of n-alkanes without an odd-over-even predominance as a result of microbial alteration (Brittingham et al, 2017;Jansen and Wiesenberg, 2017;Rao et al, 2009;Wu et al, 2019), although this should be studied more extensively. Notably, 280 the CPI does not correlate with the ACL and ratio metrics (Fig.…”
mentioning
confidence: 99%